Electronic structure of Ni-Mn-Ga magnetic shape memory alloy studied be EELS method - Ochoa-Gamboa, R.; Flores-Zuniga, H.; Espinosa-Magana, F.; Rios-Jara, D.; Glavatskyy, I.; Glavatska, N. (Functional Materials, 2006)
The evolution of 3d electronic structure associated with the martensitic transformation and ferromagnetic transition in non-stoichiometric Ni₂MnGa alloy possessing the shape magnetic memory were studied by electron-energy loss spectroscopy (EELS) and with theoretical modeling methods. The EELS spectra of Ni-Mn-Ga crystals have been obtained under in-situ heating to study the electron structure of ferromagnetic (FM) martensite, FM austenite and paramagnetic austenite. When considering the EELS spectra, the total white lines intensity L₂₃ = L₂ + L₃ as well as as well as the L₃/L₂ ratio and conclusions have been drawn on the occupancy of the 3d state fromAs L₂₃ reflects the unoccupied density of states in 3d bands, these results indicate that no charge transfer has taken place during martensitic transformation and changes in the magnetic dipole moments at phase transitions. The experimental results have shown that the magnetic dipole moment on Ni atoms decreases at the reverse martensitic transformationwhile it increases on Mn, and the charge is observed to be redistributed between Mn and Ni in agreement with ab-initio numerical calculations.